P255 Electrophysiological and behavioral monitoring of learning: An EEG and tRNS combined study. Issue 3 (March 2017) - Tatti, E.; Golemme, M.; Chrisostomou, L.D.; Panozzo, G.; Grande, G.; Di Bernardi, C. Luft; Cappelletti, M.
Abstract : Question: Improving cognitive abilities by means of training and brain stimulation has often been reported (Elmasry et al., 2015 ). However, the specific electrophysiological and cognitive processes underlying these improvements are still overlooked. In order to investigate the behavioural and electrophysiological effects of brain stimulation on learning, we designed a training study of visual working memory and inhibitory abilities. Our main goal was to characterize the behavioral and brain oscillatory correlates of training, combined or not with tRNS. Methods: Thirty healthy young participants were tested before and after being trained for 4 consecutive days. Half of the participants received training coupled with parietal brain stimulation (tRNS), half coupled with sham. We used an established retrocueing paradigm (Pertzov et al., 2013 ), which provides an index of WM precision as well as of inhibitory abilities, which are critical for memory recall (Gazzaley et al., 2005 ). Electrophysiological activity was recorded for the entire duration of the training. Frequency specific changes of the ongoing EEG activity were analysed using Morlet wavelet decomposition. Results: We found a significant amelioration in inhibitory abilities and in the precision of the memory trace, particularly in the tRNS group. Electrophysiologically, these changes were explained by parietal alpha desynchronization in both groups as well as decreased frontal theta synchronization in the tRNS group. Conclusion: Training induced changes in visual working memory and inhibitory abilities can be monitored behaviorally and electrophysiologically. Here, theta driven modulation of top-down attention and alpha driven modulation of inhibitory abilities explain tRNS and training-related changes in performance.